Constructing the (Un)Readiness of Brazilian Immigrant Children in One Elementary School. (2nd October 2021) - Oliveira, Gabrielle; Lima Becker, Mariana; Segel, Marisa
Abstract : The phrase ready to learn has been widely used and researched by scholars, policy makers, and education practitioners. School readiness, as a construct, has referred to the basic skills that children need to transition to elementary school. However, there is no consensus on which basic skills students should possess when entering kindergarten, and even less for bilingual learners. In this article, we draw on interview data from 15 staff members in one urban public elementary school in the U.S. Northeast. We focus on how teachers and staff perceived their Brazilian students' disposition in kindergarten and first grade. Most of these professionals (nine out of fifteen) were themselves of Brazilian descent, shedding light on the understudied complexities of immigrant school personnel?s positions and experiences in the multicultural landscapes of U.S. public schools.